Çağdaş İslam düşüncesinde yenilenme perspektifleri -Arap dünyası ve Hint-alt kıtası bağlamında kronolojik bir değerlendirme- - Yıldız, Semiha Selcen (My University, 2019)
İslam dünyasının 19. yüzyıldan itibaren Batı karşısında güç kaybedişi ve bunun ortaya çıkardığı siyasi, askeri, ekonomik, kültürel vb. sorunlara çözüm arayışı olarak başlayan süreç, temelde aynı sorunlar etrafında ancak değişen alt başlıklarla, farklı açılım ve yaklaşımlarla bugüne kadar devam etmiştir.İslam düşüncesinin iki asrı aşkın bir süredir devam eden bu son dönemi yirmiyi aşkın düşünürün değerlendirmeleri üzerinden siyasi bir antoloji şeklinde ele alınmıştır.

slamic world losed power agaist Europa and lived political, military, economical, cultural problems ın the 19th century. Modern Islamic Thought is reviews this proses. This proses continues until today. Thinkers ın the proses named modernist and tradionalist. All thinkers suggest different solutions but anything set great store on democratic acguisitions for Islamic world. Most of them say Islam is important for the world specially in the latter day. Because humanity needs princeples and worths of Islam. And most of them say Islam is theology of liberation for world and humanity at the present time. This exploration summarise briefly last two centuries in the history of Islamic thought context evaluations of most thinkers.
Keywords: ConsultationRenewal Perspectives; Democracy; Demokrasi; Devlet; Gelenek; Islah; Islamic philosophy; İhya; İslam felsefesi; Modern; Modernleşme; Reform; State; Şura Renewal; Tecdit; Tradition; Ümmet; Yenilenme